Descrevendo e analisando os textos escritos de língua portuguesa que compõem as unidades dos materiais didáticos dos cursos a distância - Cunha, Isabel Freitas (2009)
The purpose of this study was to analyse the texts that compound the material used in distance education courses presenting their regularities according to infrastructure, in order to characterize them as a textual genre. To do so, we are aimed at: a) describing and analysing the texts in relation to the organization of the thematic content (general plan); b) investigating the thematic content and its relation to its sequential textual organization and with the types of discourse that compound each unit. The corpus of this research, of descriptive, quantitative and interpretative nature, is formed by sixteen written units to compound the material used in distance education courses of three Brazilian universities: Centro Universitário Claretiano CEUCLAR (Batatais, SP); Universidade de Uberaba UNIUBE (Uberaba, MG) and Universidade do Sul de Santa Catarina (Palhoça, SC). The analyses is based on Bronckart s theory (2003), which states that every text is organized into three components: the general textual infrastructure, the textualization and enunciative mechanisms. The studies of Bakhtin (2003) were also used when he defines textual genres and considers constituent elements of enunciation, as follow: thematic content, linguistic resources and compositional construction. We also verified that the units are highly standardized in its general infrastructure, which was our aim in this study, beginning with the general plan, responsible for showing the thematic content organization. In addition, we observed that the dominating sequence in the units is the explicative, followed by the injuntive, argumentative and descriptive ones. Another planification form showed in these texts is the outlines. We also listed the types of discourse in the units and we verified that the theory is predominating, as well as being by the monological interactive discourse, what can help the student be interacted with the text, once in the distance learning education, teacher-student direct contact does not always occur, or it does not exist at all. So, we reached the general aim of the work, which was the characterization of the texts used in the distance graduation courses as a genre, once the way language is organized is determined by its functions in this specific context of the teachinglearning process.